Management with macroeconomic policies affecting economic development (Case in the republic of North Macedonia) - Ameti, Ilaz; Idrizi, Arsim (Edelweiss Applied Science and Technology, 2024)
Unemployment is one of the most vexing and difficult socio-economic problems faced by many countries in the world. The unemployment rate brings with it a series of problems such as: poverty, social insecurity which in turn results in a low quality of life of the population in that country, unemployment also affects the use of resources and the economic scale of a country. Due to the high rate of unemployment in the Republic of North Macedonia, macroeconomic policies have been applied as training programs with the sole aim of reducing unemployment. Creating a positive climate and creating certain mechanisms in the labor market encourages investors, local and foreign, to invest and thus create new jobs. The high rate of unemployment in this country shows us that the macroeconomic situation is fragile, but we should also note that due to the active policies of the labor market, unemployment in the Republic of North Macedonia is still decreasing, that is, it is continuous decline, which is a good sign for the recovery of our economy, but on the other hand, it is a result of immigration to other countries, mainly Western Europe. The purpose of this research is to analyze the relationship and impact that inflation and economic growth have on unemployment in the Republic of North Macedonia. To prove this connection, we have based on numerous evidences using the data for the 5-year period 2017-2022 and in the end we have come to the conclusion that in the case of the Republic of North Macedonia there is a negative relationship between inflation and unemployment also negative relationship between economic growth and unemployment.